Analysis of Digital Science Literacy Competence to Build Students' Independent Learning Creativity in Learning Process - Zurweni Zurweni; Affan Malik (EDUJAVARE: International Journal of Educational Research, 2025)
In the Industrial Era 4.0 which has entered the Society Era 5.0, mastery of Science and Technology is one of the key indicators of the success of the Indonesian nation in facing global competition. The purpose of this study is to analyze the digital literacy competency of science students using a questionnaire and digital literacy competency evaluation instrument for Chemistry Science related to independent learning within the scope of Heutagogy. This research method uses an applied mixed-method research approach conducted online and offline, using a simple random sample. The sample of this study is representative of FKIP UNJA students. The results of this study provide information that the digital literacy competency of Chemistry Education students is generally in the good category, and quite good when analyzed in terms of cognitive aspects, both in terms of attitude and also in terms of skills. Meanwhile, for general digital literacy skills, FKIP UNJA students are still low in terms of analyzing problems digitally. Policy options that can be implemented in the future are with various techniques and programs, including the use of PBL and Case Study models in the learning process, providing opportunities for students to take digital-based lectures in the Information Systems Study Program, and others through the Merdeka Belajar Kampus Merdeka program.